THE EFFECT OF DEBT TO EQUITY RATIO AND RETURN ON ASSETS ON STOCK RETURNS IN PROPERTY COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE IN 2020-2022 - Rona Bernike Br Sinuhaji; Cut Fitri Rostina; Fauzi (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
This study was conducted to test the influence of each predetermined variable, both simultaneously and partially. From a total population of 31 companies, and based on the criteria that have been set, a sample of 20 companies was obtained. This type of research is quantitative using secondary data measured on a ratio scale to be processed statistically. The analysis method used is multiple linear regression. The results of the analysis through the F test show that the Debt to Equity Ratio (DER) Return on Assets (ROA) variable simultaneously does not have a significant positive effect on stock returns. However, the results of the (partial) t-test show that DER and ROA do not have a significant influence on the stock price.